Reduction in Junctophilin 2 Expression in Cardiac Nodal Tissue Results in Intracellular Calcium-Driven Increase in Nodal Cell Automaticity. - Landstrom, Andrew P.; Yang, Qixin; Sun, Bo; Perelli, Robin M.; Bidzimou, Minu Tshyeto; Zhang, Zhushan; Aguilar-Sanchez, Yuriana; Alsina, Katherina M.; Cao, Shuyi; Reynolds, Julia O.; Word, Tarah A.; van der Sangen, Niels M.R.; et al. (Circulation-Arrhythmia and Electrophysiology, 2023)
BACKGROUND: Spontaneously depolarizing nodal cells comprise the pacemaker of the heart. Intracellular calcium (Ca2+) plays a critical role in mediating nodal cell automaticity and understanding this so-called Ca2+ clock is critical to understanding nodal arrhythmias. We previously demonstrated a role for Jph2 (junctophilin 2) in regulating Ca2+-signaling through inhibition of RyR2 (ryanodine receptor 2) Ca2+ leak in cardiac myocytes; however, its role in pacemaker function and nodal arrhythmias remains unknown. We sought to determine whether nodal Jph2 expression silencing causes increased sinoatrial and atrioventricular nodal cell automaticity due to aberrant RyR2 Ca2+ leak. METHODS: A tamoxifen-inducible, nodal tissue-specific, knockdown mouse of Jph2 was achieved using a Cre-recombinase-triggered short RNA hairpin directed against Jph2 (Hcn4:shJph2). In vivo cardiac rhythm was monitored by surface ECG, implantable cardiac telemetry, and intracardiac electrophysiology studies. Intracellular Ca2+ imaging was performed using confocal-based line scans of isolated nodal cells loaded with fluorescent Ca2+ reporter Cal-520. Whole cell patch clamp was conducted on isolated nodal cells to determine action potential kinetics and sodium-calcium exchanger function. RESULTS: Hcn4:shJph2 mice demonstrated a 40% reduction in nodal Jph2 expression, resting sinus tachycardia, and impaired heart rate response to pharmacologic stress. In vivo intracardiac electrophysiology studies and ex vivo optical mapping demonstrated accelerated junctional rhythm originating from the atrioventricular node. Hcn4:shJph2 nodal cells demonstrated increased and irregular Ca2+ transient generation with increased Ca2+ spark frequency and Ca2+ leak from the sarcoplasmic reticulum. This was associated with increased nodal cell AP firing rate, faster diastolic repolarization rate, and reduced sodium-calcium exchanger activity during repolarized states compared to control. Phenome-wide association studies of the JPH2 locus identified an association with sinoatrial nodal disease and atrioventricular nodal block. CONCLUSIONS: Nodal-specific Jph2 knockdown causes increased nodal automaticity through increased Ca2+ leak from intracellular stores. Dysregulated intracellular Ca2+ underlies nodal arrhythmogenesis in this mouse model.
EVALuna2:530480